Row 1- 1/4, 0.20
row 2- 10%, 0.10
row 3- 4/5, 0.80
row 4- 33%, 1/3
Answer:
15
Step-by-step explanation:
5:22=15:66, simply multiply 3 in the right hand side
Her estimate is lower than her actual cost because her total is 72.87 she is off by 1.72 because she only added 42,17,and 12 and forgot all about adding the cent or the .60,.38,and the .89.
9514 1404 393
Answer:
f^-1(x) = (x +4)/3
Step-by-step explanation:
The inverse function is found by swapping x and y, then solving for y.
y = 3x -4 . . . . . function y = f(x)
x = 3y -4 . . . . . inverse relation
x +4 = 3y . . . . add 4
(x +4)/3 = y . . . divide by 3. This is the inverse function
f^-1(x) = (x +4)/3